Integrated single-cell transcriptome analysis of the tumor ecosystems underlying cervical cancer metastasis - Li, Chunbo; Liu, Danyang; Yang, Shimin; Hua, Keqin (Frontiers in Immunology, 2022)
Cervical cancer (CC) is one of the most frequent female malignancies worldwide. However, the molecular mechanism of lymph node metastasis in CC remains unclear. In this study, we investigated the transcriptome profile of 51507 single cells from primary tumors, positive lymph nodes (P-LN) and negative lymph node (N-LN) using single-cell sequencing. Validation experiments were performed using bulk transcriptomic datasets and immunohistochemical assay. Our results indicated that epithelial cells in metastatic LN were associated with cell-cycle related signaling pathways, such as E2F targets, and mitotic spindle, and immune response related signaling pathways, such as allograft rejection, IL2_STAT5_signaling, and inflammatory response. However, epithelial cells exhibited high enrichment of epithelial-mesenchymal translation, oxidative phosphorylation and interferon alpha response. Then, our analysis indicated that metastasis LN exhibited an early activated tumor microenvironment (TME) characterized by the decrease of naive T cells, and increase of cytotoxicity CD8 T cells, NK cells, FOXP3+ Treg cells compared with normal LN. By comparing the differently expressed gene of macrophages between tumor and metastatic LN, we identified the C1QA+ MRC1low macrophages were enriched in tumor, but C1QA+ MRC1high enriched in metastatic LN. Finally, we demonstrated that cancer-associated fibroblasts (CAFs) in P-LN was associated with immune regulation, while CAFs in tumor underwent epithelial-mesenchymal translation. Our findings offered novel insights into the mechanism research, diagnosis and therapy of CC metastasis.